Pengaruh Kepribadian Terhadap Kreativitas Generasi Alpha - Alfiansa, Sendi; Safitri, Syiva; Aslamiah (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
This study aims to examine the impact of personality types based on the Big Five Theory of Personality on the creativity of Generation Alpha. This is a quantitative ex post facto study conducted at SMP Negeri 19 Kota Bekasi. The sampling strategy used is stratified random sampling, resulting in 128 samples from 27 classes across three grade levels. Data collection involved questionnaires with the Big Five Instrument (BFI) for personality and a self-developed creativity instrument that has been validated and reliable. The data were analyzed using multiple linear regression. The results indicate that there is an effect of the personality traits openness, conscientiousness, and agreeableness on the creativity of Generation Alpha with a significance value (Sig.) (p < 0.05), while there is no effect of extraversion and neuroticism on creativity with a significance value (Sig.) (p > 0.05). The obtained R square (R²) is 0.416, indicating that the Big Five personality traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism) account for 41.6% of the variance in creativity, while the remaining 58.4% is attributed to other factors